The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/978-3-540-44457-2_3
|View full text |Cite
|
Sign up to set email alerts
|

CP Violation in B and K Decays: 2003

Abstract: These lectures give a brief description of CP violation in B and K meson decays with particular emphasize put on the determination of the CKM matrix. The following topics will be discussed: i) The CKM matrix, the unitarity triangle and general aspects of the theoretical framework, ii) Particle-antiparticle mixing and various types of CP violation, iii) Standard analysis of the unitarity triangle, iv) The ratio ε ′ /ε, v) The most important strategies for the determination of the angles α, β and γ from B decays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…This allowed to perform a new check of the Standard Model based on the test of the unitarity of the CKM mixing matrix, the so-called unitarity triangle test of the SM. It was shown [39][40][41][42][43] that the SM with three families of quarks is in an good agreement with existing data, which include the data on the measurements of the effects of CP violation. In the unitarity triangle (UT) test the experimental values of the K L − K S mass difference ∆m K and the B dH − B dL mass difference ∆m B d are used.…”
Section: Introductionsupporting
confidence: 60%
“…This allowed to perform a new check of the Standard Model based on the test of the unitarity of the CKM mixing matrix, the so-called unitarity triangle test of the SM. It was shown [39][40][41][42][43] that the SM with three families of quarks is in an good agreement with existing data, which include the data on the measurements of the effects of CP violation. In the unitarity triangle (UT) test the experimental values of the K L − K S mass difference ∆m K and the B dH − B dL mass difference ∆m B d are used.…”
Section: Introductionsupporting
confidence: 60%
“…This framework is known as the operator product expansion, and is described in more detail in, e.g., Refs. [33,34]. In many concrete models, the operators that are most sensitive to NP are a subset of …”
Section: Model-independent Analysis Of New Physics Contributions To Lmentioning
confidence: 99%
“…This scenario has been studied in extensions of the CKM fit of the SM which includes B = 2 measurements to constrain the CKM elements V tq [256,259], in combination with many other flavour-changing processes. Including LHCb measurements [139,229] 34 the SM point [256] (prior to the LHCb results being available, a similar analysis gave a discrepancy of 3.6σ driven mainly by the anomalous dimuon asymmetry [259]). The analysis gives s consistent with the SM, within large uncertainties, whereas the more precise data in the B 0 system hint at a deviation in d (see Fig.…”
Section: Model Independent Constraints On New Physics In B Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 An up-to-date review of experimental constraints on B meson mixing can also be found in the PDG. 9 The following discussion applies to neutral mesons of any kind.…”
Section: Beauty Mixing Phenomenology In a Nutshellmentioning
confidence: 99%